Inhibition of the Aquaporin-1 Cation Conductance by Selected Furan Compounds Reduces Red Blood Cell Sickling - Pak Hin Chow; Charles D. Cox; Charles D. Cox; Jinxin V. Pei; Nancy Anabaraonye; Saeed Nourmohammadi; Sam W. Henderson; Boris Martinac; Boris Martinac; Osheiza Abdulmalik; Andrea J. Yool (Frontiers Media S.A., 2022)
In sickle cell disease (SCD), the pathological shift of red blood cells (RBCs) into distorted morphologies under hypoxic conditions follows activation of a cationic leak current (Psickle) and cell dehydration. Prior work showed sickling was reduced by 5-hydroxylmethyl-2-furfural (5-HMF), which stabilized mutant hemoglobin and also blocked the Psickle current in RBCs, though the molecular basis of this 5-HMF-sensitive cation current remained a mystery. Work here is the first to test the hypothesis that Aquaporin-1 (AQP1) cation channels contribute to the monovalent component of Psickle. Human AQP1 channels expressed in Xenopus oocytes were evaluated for sensitivity to 5-HMF and four derivatives known to have differential efficacies in preventing RBC sickling. Ion conductances were measured by two-electrode voltage clamp, and osmotic water permeability by optical swelling assays. Compounds tested were: 5-HMF; 5-PMFC (5-(phenoxymethyl)furan-2-carbaldehyde); 5-CMFC (5-(4-chlorophenoxymethyl)furan-2-carbaldehyde); 5-NMFC (5-(2-nitrophenoxymethyl)-furan-2-carbaldehyde); and VZHE006 (tert-butyl (5-formylfuran-2-yl)methyl carbonate). The most effective anti-sickling agent, 5-PMFC, was the most potent inhibitor of the AQP1 ion conductance (98% block at 100 µM). The order of sensitivity of the AQP1 conductance to inhibition was 5-PMFC > VZHE006 > 5-CMFC ≥ 5-NMFC, which corresponded with effectiveness in protecting RBCs from sickling. None of the compounds altered AQP1 water channel activity. Combined application of a selective AQP1 ion channel blocker AqB011 (80 µM) with a selective hemoglobin modifying agent 5-NMFC (2.5 mM) increased anti-sickling effectiveness in red blood cells from human SCD patients. Another non-selective cation channel known to be expressed in RBCs, Piezo1, was unaffected by 2 mM 5-HMF. Results suggest that inhibition of AQP1 ion channels and capacity to modify hemoglobin are combined features of the most effective anti-sickling agents. Future therapeutics aimed at both targets could hold promise for improved treatments for SCD.